Kublihan a holistic and self-sustainable mixed-use youth care center in Baguio City - Que, Donna Leanne S. (College of Architecture, University of the Philippines Diliman, 2023)
The number of street children in the Philippines is rapidly increasing, especially with the country's worsening poverty. Street children include anyone under the age of 18 who is orphaned and homeless, have families but are homeless, and have homes but work on the streets. They are considered most vulnerable as they are exposed to various physical, sexual, and emotional dangers (Meribole, 2020). And although there are several efforts from different government agencies and non-profit organizations to ensure their well-being, there remains a lack of support from related stakeholders. Adding to this are negative effects of the country's unprogressive orphanage system -- where most orphanages are underdeveloped and rely on donations to sustain operation (Kaiman and De Leon, 2016). Furthermore, existing orphanages and youth shelters are in old/compact buildings which do not address current needs of Filipino children. All these limited resources make it harder to support street children, leaving them unable to access opportunities for a well-rounded and self-sustainable development. This project addresses the issue of lack and inefficiency of institutions for street children care through a holistic child-rights based approach. With the goal of modernizing youth care institutions to fit current needs and paradigms, this project proposes an architectural solution in a form of a mixed-used youth care center which integrates organic and vertical forms, and a farm-to-table restaurant into flexible housing and interactive spaces. This done through conducting qualitative research on current needs and issues of Filipino street children and existing youth shelters/orphanages, as well as secondary data analysis of topics on urban agriculture and farm-to-table concepts, along with an in-depth review of prevailing codes and standards. Through this project, the street children are ensured their rights, and given housing, learning and socializing opportunities--all contributing to a more holistic and self-sustaining growth and development.